Guts Imbalance Imbalances the Brain: A Review of Gut Microbiota Association With Neurological and Psychiatric Disorders - Mitrea, Laura; Nemeş, Silvia-Amalia; Szabo, Katalin; Teleky, Bernadette-Emőke; Vodnar, Dan-Cristian (Frontiers in Medicine, 2022)
In the last ten years, there has been a growing interest regarding the relationship between gut microbiota, brain, and neurological-associated affections. As multiple preclinical and clinical researches highlight the gut microbiota’s potential to modulate the general health state, it goes without saying that gut microbiota plays a significant role in neurogenesis, mental and cognitive development, emotions, behavior, and in the progression of neuropsychiatric illnesses. Gut microbiota produces important biologic products which through the gut-brain axis are directly connected with the appearance and the evolution of neurological and psychiatric disorders such as depression, anxiety, bipolar disorders, autism, schizophrenia, Parkinson's disease, Alzheimer's disease, dementia, multiple sclerosis, or epilepsy. In this work, are reviewed the most recent in-sights regarding the link between gut microbiota and the brain, and the microbiome’s role in shaping the development of the most common neurological and psychiatric illnesses. Moreover, special attention is paid to the use of probiotic formulations as a potential non-invasive therapeutic opportunity for the prevention and management of neuropsychiatric-associated affections.